Mantikê : studies in ancient divination - Johnston, Sarah Iles, 1957-; Struck, Peter T. (Religions in the Graeco-Roman world, 2005)
This book is a collection of studies by scholars Greek, Roman, Egyptian, and early Christian religions on the topic of divination. Its topics range from necromancy to dice rolling, free-lance diviners to Delphi, and includes treatments from the Archaic period to Late Antiquity.